After you [large type] : a novel - Moyes, Jojo, 1969- (Thorndike Press, 2015)
Louisa Clark is no longer just an ordinary girl living an ordinary life. After the transformative six months spent with Will Traynor, she is struggling without him. When an extraordinary accident forces Lou to return home to her family, she can't help but feel she's right back where she started. Her body heals, but Lou herself knows that she needs to be kick-started back to life. Which is how she ends up in a church basement with the members of the Moving On support group, who share insights, laughter, frustrations, and terrible cookies. They will also lead her to the strong, capable Sam Fielding -- the paramedic whose business is life and death, and the one man who might be able to understand her. Then a figure from Will's past appears and hijacks all her plans, propelling her into a very different future.